Misuse of Residence Permits by Foreign Citizens in the Perspective Law Concerning Immigration - Amirullah, Trisakti Rizky; Handayati, Nur; Prawesthi, Wahyu (Global Education Journal, 2025)
The misuse of residence permits by foreign nationals (WNA) in Indonesia is a critical issue that impacts public order and national sovereignty. This study aims to analyze the forms of residence permit abuse by foreign nationals from an immigration law perspective, and the legal actions imposed under Law Number 6 of 2011 concerning Immigration. This study uses a normative legal research type. Normative legal research focuses on the study of legal principles, norms, and applicable laws and regulations. The results show that misuse of residence permits includes overstaying, working without permission, document falsification, and fake marriages. Legal actions include administrative sanctions such as deportation and fines, as well as criminal sanctions for serious violations. Although regulations are adequate, law enforcement is not optimal due to weak inter-agency coordination and a lack of deterrent effect. Therefore, strengthened supervision, firm criminal enforcement, and cross-sectoral cooperation are needed.